Optimized Reaction Conditions Enable the Hydration of Non‐natural Substrates by the Oleate Hydratase from Elizabethkingia meningoseptica. Issue 5 (31st January 2017) - Demming, Rebecca M.; Otte, Konrad B.; Nestl, Bettina M.; Hauer, Bernhard
Abstract: The oleate hydratase from Elizabethkingia meningoseptica ( Em ‐OAH) catalyzes the hydration of oleic acid (C18) to ( R )‐10‐hydroxystearic acid. In previous work, low activity of Em ‐OAH towards chemically synthesized ( Z )‐undec‐9‐enoic acid (C11) was observed. Product formation in the hydration of the truncated C11 substrate was improved by optimizing the reaction conditions by applying statistical experiment design. Optimized reaction conditions resulted in a 2.8‐fold increase in product formation in just one quarter of the time (64 % conversion in 28 h). The applicability has been assessed in the upscaling of the conversion of ( Z )‐undec‐9‐enoic acid to ( S )‐10‐hydroxyundecanoic acid (132 mg product, >95 % purity). Reaction conditions developed for the hydration of C11 facilitated the first hydration of non‐natural alkenes. By using a fatty acid dummy substrate, 1‐decene was successfully hydrated to ( S )‐2‐decanol with excellent stereoselectivity and 50 % conversion after four days of incubation. Abstract : Selective addition of water : The formation of ( S )‐10‐hydroxyundecanoic acid and ( S )‐2‐decanol with high yield and excellent stereoselectivity by oleate hydratase from E. meningoseptica is reported as a first step towards the hydration of short‐chain non‐natural substrates.